Priorities for lung transplantation research: a James Lind Alliance priority-setting partnership between patients, caregivers, and clinicians in Canada - Margret I. Michaels; Kieran Halloran; Lea Harper; Nikki Marks; Celine Bergeron; Basil Nasir; Dima Kabbani; Laura van den Bosch; Alim Hirji; Rhea A. Varughese; Jason Weatherald (JHLT Open)
This study employed the James Lind Alliance Priority Setting Partnership methodology to identify and prioritize research priorities in lung transplantation through engagement of pre- and post-lung transplant patients, caregivers, and clinicians in Canada. An initial survey collected 490 questions from 204 respondents, which were collated into 117 summary questions. After removing duplicates and conducting evidence checks, 25 verified uncertainties were discussed at a final workshop, resulting in a consensus-based Top 10 list of research priorities. Key priorities addressed the need to improve immunosuppression regimens, patient education, lung allograft dysfunction, and donor lung availability. This first-of-its-kind initiative in lung transplantation created a stakeholder-driven research agenda that better aligns future research with patient needs. The findings establish a foundation for more patient-centered lung transplantation research.